2021
DOI: 10.1007/s10157-021-02123-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcomes of COVID-19 patients with acute kidney injury: a tertiary centre experience from South India

Abstract: Aim The rates of development of acute kidney injury (AKI) in COVID-19 have been variably reported from across the world. Prevalence and outcomes of AKI in hospitalised COVID-19 patients in India has not been studied well. Methods This was a retrospective observational study amongst adult hospitalised COVID-19 patients admitted at a tertiary care centre between May 1 and October 31, 2020. We estimated the prevalence of AKI and outcomes including mortality and acute kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
5
17
1
2
Order By: Relevance
“…In our study, among patients who developed AKI, 54.6% required ICU care, 72.09% required ventilation, and 24.4% died. Thus, our patients overall mortality rate in AKI is consistent with the study conducted by Sindhu and Prasad[ 12 ] but is lower than other studies[ 13 25 ] that reported mortality rates between 35% and 45%. This might be due to the fact that more patients in our study had a lower stage of AKI than those in other studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, among patients who developed AKI, 54.6% required ICU care, 72.09% required ventilation, and 24.4% died. Thus, our patients overall mortality rate in AKI is consistent with the study conducted by Sindhu and Prasad[ 12 ] but is lower than other studies[ 13 25 ] that reported mortality rates between 35% and 45%. This might be due to the fact that more patients in our study had a lower stage of AKI than those in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…The reported incidence of AKI as between 1% and 42% among those infected with COVID-19 is currently only based on reports from small case series and retrospective studies from China,[ 21 ] Europe,[ 22 23 ] the United States,[ 19 ] and India. [ 12 13 24 ] The variances between previous studies and our investigation might be related due to variances in patient populations and geographic location. Our AKI rates are consistent with other recent studies from India,[ 12 13 ] which found that AKI incidence is between 7 and 7.2%.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We performed a systematic search in PubMed to identify recently published large cohort studies related to AKI in patients with COVID-19. We used the search terms “Coronavirus”, “COVID-19”, “SARS-CoV-2”, “acute kidney damage”, “acute kidney injury”, “AKI” and found that the incidence of AKI was higher in severe COVID-19 patients and AKI was strongly associated with high mortality ( Table 1 ) ( Bell et al., 2021 ; Chen et al., 2021 ; Jewell et al., 2021 ; Kilis‐pstrusinska et al., 2021 ; Marques et al., 2021 ; Procaccini et al., 2021 ; Rahimzadeh et al., 2021 ; Scarpioni et al., 2021 ; Sullivan et al., 2021 ; Strohbehn et al., 2021 ; Wan et al., 2021 ; Hung et al., 2022 ; Hsu et al., 2022 ; Sindhu et al., 2022 ). Many possible mechanisms for COVID-19-induced kidney injury have been proposed, including the direct kidney injury mediated by the combination of virus and ACE2.…”
Section: Introductionmentioning
confidence: 99%